Wood flame-retardant treatment method based on phosphorus-nitrogen-silicon composite reaction and flame-retardant wood
Through the wood flame retardant treatment method based on phosphorus, nitrogen and silicon composite reaction, the impregnation treatment of sodium silicate/glucose mixed aqueous solution, MEL aqueous solution and PBTCA aqueous solution, the problems of traditional flame retardant precipitation and anti-halogenation are solved, and the efficient flame retardant effect of wood is achieved.
Patent Information
- Application Number
- CN202411678372.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-04-04
AI Technical Summary
Traditional wood flame retardants have precipitation and anti-halogenation phenomena, resulting in a decrease in flame retardant efficiency.
The wood flame retardant treatment method based on phosphorus, nitrogen and silicon composite reaction is adopted, and the immersion treatment of sodium silicate/glucose mixed aqueous solution, MEL aqueous solution and PBTCA aqueous solution is caused to react in wood to form an expanded flame retardant system.
It effectively solves the precipitation and anti-halogenation phenomena of flame retardant, improves the flame retardant efficiency of wood, reduces the heat release rate and smoke release rate, and enhances the non-combustibility.
Smart Images

Figure CN119748581A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a wood flame retardant treatment technology, and in particular to a wood flame retardant treatment method based on phosphorus-nitrogen-silicon composite reaction and flame retardant wood. Background Art
[0002] Traditional flame retardants for wood have the phenomenon of precipitation and anti-halogenation, which seriously affects the flame retardant efficiency and the later use of wood products. An effective solution is yet to be proposed by compounding composite reactive flame retardants and other flame retardant elements. Summary of the invention
[0003] The present invention is developed in view of the above problems, and its purpose is to solve the problem of reduced flame retardant efficiency caused by the precipitation and halogenation of flame retardants in the past by compounding composite reactive flame retardants and other flame retardant elements.
[0004] Firstly, a method for flame retardant treatment of wood based on phosphorus-nitrogen-silicon composite reaction is provided. In the method, the wood is successively impregnated with a sodium silicate / glucose mixed aqueous solution, a MEL aqueous solution and a PBTCA aqueous solution and then dried to allow the following reaction to occur between MEL and PBTCA in the wood.
[0005]
[0006] Specifically, the concentration of the sodium silicate / glucose mixed aqueous solution is 2-3 wt% sodium silicate / 12-13 wt% glucose, the concentration of the MEL aqueous solution is 1.5-2.5 wt% and the concentration of the PBTCA aqueous solution is 45-55 wt%.
[0007] Optionally, the sodium silicate / glucose mixed aqueous solution is obtained by mixing a sodium silicate aqueous solution with a concentration of 4.5 to 5 wt % and a glucose aqueous solution with a concentration of 20 to 30 wt % in a mass ratio of (1 to 1.01):1.
[0008] More specifically, the solid-liquid mass ratio of wood to sodium silicate / glucose mixed aqueous solution is (200-300):(2040-2050), the solid-liquid mass ratio of wood to MEL aqueous solution is (200-300):(1100-1300), and the solid-liquid mass ratio of wood to PBTCA aqueous solution is (200-300):(900-1100).
[0009] More specifically, the concentrations of the sodium silicate / glucose mixed aqueous solution were: sodium silicate: 2.4 wt %, glucose: 12.2 wt %, the concentration of the MEL aqueous solution was 2 wt %, and the concentration of the PBTCA aqueous solution was 50 wt %.
[0010] More specifically, the solid-liquid mass ratio of wood to sodium silicate / glucose mixed aqueous solution is (200-300):2045, the solid-liquid mass ratio of wood to MEL aqueous solution is (200-300):1200, and the solid-liquid mass ratio of wood to PBTCA aqueous solution is (200-300):1000.
[0011] Specifically, the immersion treatment includes: (1) immersing the wood in a sodium silicate / glucose mixed aqueous solution, vacuuming to -0.10 to -0.09 MPa and maintaining it for 30 to 50 minutes, then pressurizing it to 1.2 to 1.25 PMa and maintaining it for 2 to 4 hours, and then washing it with clean water after taking it out; (2) drying the wood treated with (1) and immersing it in a MEL aqueous solution, vacuuming to -0.15 to -0.09 MPa and maintaining it for 30 to 50 minutes, then pressurizing it to 1.2 to 1.25 PMa and maintaining it for 2 to 4 hours, and then washing it with clean water after taking it out; (3) drying the wood treated with (2) and immersing it in a PBTCA aqueous solution, vacuuming to -0.15 to -0.09 MPa and maintaining it for 30 to 50 minutes, then pressurizing it to 1.2 to 1.25 PMa and maintaining it for 2 to 4 hours, and then washing it with clean water after taking it out.
[0012] Specifically, the drying comprises: placing the wood treated in (3) into a drying box and drying it at a temperature of 70 to 80° C. for 4 to 5 hours.
[0013] Also provided is a flame retardant wood obtained by being treated by any one of the above methods.
[0014] MP itself contains phosphorus and nitrogen elements, which together with the carbon elements of glucose form an intumescent flame retardant system (PNC). After being heated, MP can produce an inorganic acid source to catalyze the dehydration of the carbon source (glucose), thereby forming an intumescent carbon layer. At the same time, the gas source produces non-flammable gas, thereby protecting the substrate from fire damage.
[0015] Sodium silicate and the acid source produce a synergistic effect, enhancing the hardening of the carbon layer, forming a silicon oxide network at high temperature, and the dense Si-O-Si network can inhibit the release of smoke, achieving the effect of smoke suppression and efficiency enhancement. And through the first step of impregnation of silicate, it can play a good role as a filling flame retardant, which acts on the wood fiber material to enhance the non-combustibility, thereby building a permeable dense carbon layer between the wood fiber and the expanded carbon layer during combustion. DETAILED DESCRIPTION
[0016] The invention synthesizes MP from melamine (MEL) impregnated in wood and 2-phospho-1,2,4-tricarboxylic acid butane (PBTCA).
[0017] The structural formula of MP:
[0018]
[0019] Embodiment 1:
[0020] 1. Preparation of impregnation solution:
[0021] Add 50 g of sodium silicate and 250 g of glucose to 995 g of water and stir the mixture for 30 minutes at 25°C to obtain a mixed aqueous solution A of sodium silicate and glucose; add 20 g of MEL to 1000 g of water and stir for 30 minutes to obtain a MEL aqueous solution B; add 500 g of PBTCA to 500 g of water and stir for 30 minutes to obtain a PBTCA aqueous solution C.
[0022] 2. Impregnation process
[0023] 200 g of poplar veneer was immersed in solution A, the immersion tank containing the wood sample was evacuated to -0.09 MPa and maintained for 30 min, and then pressurized to 1.2 PMa by an air compressor and maintained for 2 h. The treated sample was taken out and washed with clean water.
[0024] After washing, the veneer was dried for a period of time and then immersed in solution B. The immersion tank containing the wood was evacuated to -0.09 MPa and maintained for 30 minutes, pressurized to 1.2 MPa by an air compressor and maintained for 2 hours, and then taken out and washed with clean water.
[0025] Next, the veneer was washed and dried for a period of time and then immersed in solution C. The impregnation tank containing the wood was evacuated to 0.09 MPa and maintained for 30 minutes, and then pressurized to 1.2 MPa by an air compressor and maintained for 2 hours. After being taken out, it was washed with clean water and placed in a drying oven for drying at 70°C for 4 hours.
[0026] Flame retardant properties:
[0027] 1-Compared with pure wood (275.5kw / m 2 ), in this case, the flame retardant wood treated with glucose, sodium silicate and MP (160.6kw / m 2 ), the peak heat release rate decreased by 41.7%;
[0028] 2-With simple wood (0.03m 2 / s) compared with the flame retardant wood (0.012m / s) treated with glucose, sodium silicate and MP compound. 2 / s), and its peak smoke release rate decreased by 60.0%;
[0029] 3- Oxygen Index:
[0030] Ordinary single board: 22.1%
[0031] This example: 35.8%
[0032] Embodiment 2:
[0033] 1. Preparation of impregnation solution:
[0034] Add 60 g of sodium silicate and 300 g of glucose to 995 g of water and stir the mixture for 50 minutes at 25°C to obtain a mixed aqueous solution A of sodium silicate and glucose; add 30 g of MEL to 1000 g of water and stir for 50 minutes to obtain a MEL aqueous solution B; add 800 g of PBTCA to 500 g of water and stir for 50 minutes to obtain a PBTCA aqueous solution C.
[0035] 2. Impregnation process
[0036] 300 g of eucalyptus veneer was immersed in solution A, the immersion tank containing the wood sample was evacuated to -0.10 MPa for 50 min, pressurized to 1.25 PMa by an air compressor for 4 h, and the treated sample was taken out and washed with clean water.
[0037] After washing, the veneer was dried for a period of time and then immersed in solution B. The immersion tank containing the wood was evacuated to -0.15 MPa and maintained for 50 minutes, pressurized to 1.25 MPa by an air compressor and maintained for 4 hours, and then taken out and washed with clean water.
[0038] Next, the veneer is washed and dried for a period of time and then immersed in solution C. The impregnation tank containing the wood is evacuated to 0.15 MPa and maintained for 50 minutes, and then pressurized to 1.25 MPa by an air compressor and maintained for 4 hours. After being taken out and washed with clean water, it is placed in a drying oven and dried at 80°C for 5 hours.
[0039] Flame retardant properties:
[0040] 1-Compared with pure wood (275.5kw / m 2 ), in this case, the flame retardant wood treated with glucose, sodium silicate and MP (151.7kw / m 2 ), the peak heat release rate decreased by 44.9%;
[0041] 2-With simple wood (0.03m 2 / s) compared with the flame retardant wood (0.0116m / s) treated with glucose, sodium silicate and MP compound. 2 / s), and its peak smoke release rate decreased by 61.3%;
[0042] 3- Oxygen Index:
[0043] Ordinary single board: 22.1%
[0044] This example: 36.2%
[0045] Comparative Example 1:
[0046] 1. Preparation of impregnation solution:
[0047] 1) Add 20 g of MEL to 1000 g of water and stir for 30 minutes to obtain MEL aqueous solution B;
[0048] 2) adding 500 g of PBTCA to 500 g of water and stirring for 30 minutes to obtain PBTCA aqueous solution C;
[0049] 2. Dipping treatment:
[0050] Immerse 200g of wood in solution B, evacuate the immersion tank containing the wood to 0.09MPa and maintain it for 30min. Pressurize it to 1.2MPa with an air compressor and maintain it for 2h. After taking it out, wash it with clean water.
[0051] Next, the veneer is washed and aired for a period of time, then immersed in solution C, and the immersion tank containing the wood is evacuated to 0.09MPa for 30 minutes. The air compressor is used to pressurize it to 1.2MPa for 2 hours, and then it is taken out, washed with clean water, dried, and placed in a drying oven at 70°C for 4 hours.
[0052] Flame retardant properties:
[0053] 1-Compared with pure poplar (275.5kw / m 2 ), the flame retardant wood treated in this example (203.7kw / m 2 ), the peak heat release rate decreased by 26.1%;
[0054] 2-With simple poplar (0.03m 2 / s), the peak smoke release rate of the flame-retardant wood treated in this example (0.017m2 / s) was reduced by 43.3%;
[0055] 3- Oxygen Index:
[0056] Ordinary single board: 22.1%
[0057] This example: 30.2%
[0058] Comparative Example 2:
[0059] 1. Preparation of impregnation solution
[0060] 50 g of sodium silicate and 250 g of glucose were added to 995 g of water and 750 g of water respectively, and the two were mixed and stirred at 25° C. for 30 minutes to obtain a mixed aqueous solution A of sodium silicate and glucose;
[0061] 2. Impregnation treatment
[0062] Immerse 200 g of wood in solution A, evacuate the immersion tank containing the wood sample to -0.09 MPa and maintain it for 30 min, pressurize it to 1.2 PMa using an air compressor and maintain it for 2 h, take out the treated sample, wash it with clean water and dry it.
[0063] Flame retardant properties:
[0064] 1-Compared with pure eucalyptus (275.5kw / m 2 ), the flame retardant wood treated in this example (225.8kw / m 2 ), the peak heat release rate decreased by 18.0%;
[0065] 2-With simple eucalyptus (0.03m 2 / s) compared with the flame retardant wood treated in Example 2 (0.034m 2 / s), the peak value of smoke release rate increased instead of decreased;
[0066] 3- Oxygen Index:
[0067] Ordinary single board: 22.1%
[0068] This example: 26.4%
[0069] Comparative Example 3:
[0070] Add 50 g of sodium silicate and 250 g of glucose to 995 g of water and stir the mixture for 30 minutes at 25°C to obtain a mixed aqueous solution A of sodium silicate and glucose; add 20 g of MEL to 1000 g of water and stir for 30 minutes to obtain a MEL aqueous solution B; add 500 g of PBTCA to 500 g of water and stir for 30 minutes to obtain a PBTCA aqueous solution C.
[0071] 2. Impregnation process
[0072] 200 g of poplar veneer was immersed in solution B, the immersion tank containing the wood sample was evacuated to -0.09 MPa for 30 min, pressurized to 1.2 PMa by an air compressor for 2 h, and the treated sample was taken out and washed with clean water.
[0073] After washing, the veneer was dried for a period of time and then immersed in solution C. The immersion tank containing the wood was evacuated to -0.09 MPa for 30 minutes, pressurized to 1.2 MPa by an air compressor for 2 hours, and then taken out and washed with clean water.
[0074] Next, the veneer was washed and dried for a period of time and then immersed in solution A. The impregnation tank containing the wood was evacuated to 0.09 MPa and maintained for 30 minutes, and then pressurized to 1.2 MPa by an air compressor and maintained for 2 hours. After being taken out, it was washed with clean water and placed in a drying oven for drying at 70°C for 4 hours.
[0075] Flame retardant properties:
[0076] 1-Compared with Example 1 (160.6kw / m 2 ), the peak heat release rate in this case (171.5m 2 / s) increased by 6.8%%;
[0077] 2-Compared with Example 1 (0.012m 2 / s) compared with the peak smoke release rate in this case (0.0124m 2 / s) increased by 3.3%%;
[0078] 3-Oxygen Index: 32.8%
[0079] Comparative Example 4:
[0080] 1. Preparation of impregnation solution:
[0081] Add 50 g of sodium silicate and 250 g of glucose to 995 g of water and stir the mixture for 30 minutes at 25°C to obtain a mixed aqueous solution A of sodium silicate and glucose; add 20 g of MEL to 1000 g of water and stir for 30 minutes to obtain a MEL aqueous solution B; add 500 g of PBTCA to 500 g of water and stir for 30 minutes to obtain a PBTCA aqueous solution C.
[0082] 2. Impregnation process
[0083] 200 g of poplar veneer was immersed in solution A, the immersion tank containing the wood sample was evacuated to -0.09 MPa and maintained for 30 min, and then pressurized to 1.2 PMa by an air compressor and maintained for 2 h. The treated sample was taken out and washed with clean water.
[0084] After washing, the veneer was dried for a period of time and then immersed in solution B. The immersion tank containing the wood was evacuated to -0.09 MPa and maintained for 30 minutes, pressurized to 1.2 MPa by an air compressor and maintained for 2 hours, and then taken out and washed with clean water.
[0085] Next, the veneer is washed and aired for a period of time and then immersed in solution C. The immersion tank containing the wood is evacuated to 0.09 MPa and maintained for 30 minutes, pressurized to 1.2 MPa by an air compressor and maintained for 2 hours. After being taken out, it is washed with clean water and dried without high-temperature drying.
[0086] Flame retardant properties:
[0087] 1-Compared with Example 1 (160.6kw / m 2 ), the peak heat release rate in this case (183.7kw / m 2 ) increased by 14.4%;
[0088] 2-Compared with Example 1 (0.012m 2 / s) compared with the peak smoke release rate in this case (0.0128m 2 / s) increased by 6.7%;
[0089] 3-Oxygen Index: 27.8%
[0090] Comparative Example 5:
[0091] 1. Preparation of impregnation solution:
[0092] Add 250 g of glucose to 750 g of water and stir for 30 minutes to obtain glucose aqueous solution A; add 20 g of MEL to 1000 g of water and stir for 30 minutes to obtain MEL aqueous solution B; add 500 g of PBTCA to 500 g of water and stir for 30 minutes to obtain PBTCA aqueous solution C.
[0093] 2. Impregnation process
[0094] 200 g of poplar veneer was immersed in solution A, the immersion tank containing the wood sample was evacuated to -0.09 MPa and maintained for 30 min, and then pressurized to 1.2 PMa by an air compressor and maintained for 2 h. The treated sample was taken out and washed with clean water.
[0095] After washing, the veneer was dried for a period of time and then immersed in solution B. The immersion tank containing the wood was evacuated to -0.09 MPa and maintained for 30 minutes, pressurized to 1.2 MPa by an air compressor and maintained for 2 hours, and then taken out and washed with clean water.
[0096] Next, the veneer was washed and dried for a period of time and then immersed in solution C. The impregnation tank containing the wood was evacuated to 0.09 MPa and maintained for 30 minutes, and then pressurized to 1.2 MPa by an air compressor and maintained for 2 hours. After being taken out, it was washed with clean water and placed in a drying oven for drying at 70°C for 4 hours.
[0097] Flame retardant properties:
[0098] 1-Compared with Example 1 (160.6kw / m 2 ), the peak heat release rate in this case (192.46kw / m 2 ) increased by 19.8%;
[0099] 2-Compared with Example 1 (0.012m 2 / s) compared with the peak smoke release rate in this case (0.017m 2 / s) increased by 41.7%%;
[0100] 3-Oxygen Index: 31.1%
Claims
1. A method for treating wood flame retardant based on phosphorus-nitrogen-silicon composite reaction, characterized in that: The wood is impregnated with a sodium silicate / glucose mixed aqueous solution, a MEL aqueous solution and a PBTCA aqueous solution in sequence and then dried to allow the following reaction to occur between MEL and PBTCA in the wood.
2. The method of claim 1, wherein: The concentration of sodium silicate / glucose mixed aqueous solution is: Sodium silicate: 2-3wt% Glucose: 12-13 wt%, The concentration of MEL aqueous solution is 1.5-2.5 wt%, The concentration of the PBTCA aqueous solution is 45 to 55 wt %.
3. The method of claim 2, wherein: The solid-liquid mass ratio of wood to sodium silicate / glucose mixed aqueous solution is (200-300):(2040-2050). The solid-liquid mass ratio of wood to MEL aqueous solution is (200-300):(1100-1300). The solid-liquid mass ratio of wood to PBTCA aqueous solution is (200-300):(900-1100).
4. The method of claim 1, wherein: The concentration of sodium silicate / glucose mixed aqueous solution is: Sodium silicate: 2.4wt% Glucose: 12.2wt%, The concentration of MEL aqueous solution is 2wt%, The concentration of the PBTCA aqueous solution was 50 wt %.
5. The method of claim 4, wherein: The solid-liquid mass ratio of wood to sodium silicate / glucose mixed aqueous solution is (200-300):2045. The solid-liquid mass ratio of wood to MEL aqueous solution is (200-300):1200. The solid-liquid mass ratio of wood to PBTCA aqueous solution is (200-300):1000.
6. The method of claim 3, wherein: The impregnation treatment comprises: (1) Immerse the wood in a sodium silicate / glucose mixed aqueous solution, evacuate to -0.10 to -0.09 MPa and maintain for 30 to 50 minutes, then pressurize to 1.2 to 1.25 PMa and maintain for 2 to 4 hours, then take out and wash with clean water; (2) After the wood treated in (1) is dried, it is immersed in the MEL aqueous solution, evacuated to -0.15 to -0.09 MPa and maintained for 30 to 50 minutes, then pressurized to 1.2 to 1.25 PMa and maintained for 2 to 4 hours, and then taken out and washed with clean water; (3) The wood treated in (2) is dried and immersed in a PBTCA aqueous solution, evacuated to -0.15 to -0.09 MPa and maintained for 30 to 50 min, then pressurized to 1.2 to 1.25 PMa and maintained for 2 to 4 h. After being taken out, the wood is washed with clean water.
7. The method of claim 6, wherein: The drying comprises: The wood treated in (3) is placed in a drying oven and dried at 70-80°C for 4-5 hours.
8. Flame-retardant wood obtained by treatment with the method according to any one of claims 1 to 7.